2022
DOI: 10.1021/acs.chemmater.2c01352
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Process for Structuring and Functionalizing Ordered Mesoporous Silica to Achieve Superprotonic Conductivity

Abstract: Polyacid-functionalized inorganic mesoporous materials have attracted considerable interest as catalysts, permselective molecular sieves, or drug carriers. Despite the great interest, their synthesis into ordered mesostructures incorporating polyacids densely and homogeneously distributed in the mesopores is a challenge. Moreover, their properties as conductors for energy applications remain completely unexplored. Here, we report an efficient, one-shot environmentally friendly synthesis route to prepare ordere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The functionalization of polyacids is achieved through the sol–gel approach [ 93 , 94 ]. For example, Richard et al reported [ 95 ] the utilization of a robust polyacid with a precisely controlled length—namely, polystyrene sulfonic acid (PSS)—as the raw polyacid material, while they employed a complex consisting of polyacid-based dihydrophilic block copolymer (DHBC) and an oppositely charged polyelectrolyte as a co-template via the sol–gel process for the preparation of polyacid-functionalized mesoporous silica. The study revealed the successful formation of strong polyacid mesoporous silica (PIC/PSS).…”
Section: Applications Of Mesoporous Silicamentioning
confidence: 99%
See 1 more Smart Citation
“…The functionalization of polyacids is achieved through the sol–gel approach [ 93 , 94 ]. For example, Richard et al reported [ 95 ] the utilization of a robust polyacid with a precisely controlled length—namely, polystyrene sulfonic acid (PSS)—as the raw polyacid material, while they employed a complex consisting of polyacid-based dihydrophilic block copolymer (DHBC) and an oppositely charged polyelectrolyte as a co-template via the sol–gel process for the preparation of polyacid-functionalized mesoporous silica. The study revealed the successful formation of strong polyacid mesoporous silica (PIC/PSS).…”
Section: Applications Of Mesoporous Silicamentioning
confidence: 99%
“… ( a ) TEM image and ( b ) SEM image of the polyacid functionalized mesoporous silica (denoted MesoPIC-PSS). MesoPIC-PSS sorption isotherms of ( c ) nitrogen measured at 77 K and related pore size distribution and ( d ) water measured at 298 K. ( e ) The schematic illustration of the integrated process for structuring and functionalizing mesoporous silica to achieve super-protonic conductivity [ 95 ]. Copyright 2022, American Chemical Society.…”
Section: Figurementioning
confidence: 99%
“…Géradin and coworkers [ 15 ] used an in situ mesopore functionalization approach [ 16 ] to integrate a polyion electrostatic complex consisting of a sulfonic acid‐bearing polyacid‐based double‐hydrophilic block copolymer and an oppositely charged polyelectrolyte for structure‐directing, functionalization, and mesopore generation of mesoporous silica. They achieved proton conductivities of up to 0.024 S cm −1 at 363 K/95% relative humidity with an environmentally friendly one‐shot synthesis procedure.…”
Section: Introductionmentioning
confidence: 99%